2016
DOI: 10.1177/0954405416681822
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a tungsten carbide–based self-lubricant cutting tool

Abstract: Tungsten carbide cutting tools with and without solid lubricant (WC-10Co-5CaF 2 and WC-10Co) were developed inhouse via powder metallurgy. The developed cutting tools and a commercial WC-10Co cutting tool were used to machine cylindrical AISI 1020 steel material under dry conditions. The cutting force and average cutting tool temperature were continuously measured. The cutting tool flank surface and chip morphology after specific tool life (5 min of cutting) were examined to understand tool wear. The flank wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(51 reference statements)
2
4
0
Order By: Relevance
“…Tool with 5 wt% (CaF 2 ) showed highest rupture strength proving suitable for usage as cutting tool. Similar results were reported by Muthuraja and Senthilvelan (2018).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tool with 5 wt% (CaF 2 ) showed highest rupture strength proving suitable for usage as cutting tool. Similar results were reported by Muthuraja and Senthilvelan (2018).…”
Section: Introductionsupporting
confidence: 92%
“…Tool with 5 wt% (CaF 2 ) showed highest rupture strength proving suitable for usage as cutting tool. Similar results were reported by Muthuraja and Senthilvelan (2018). Jianxin et al (2009) made micro holes on rake and flank face of cemented carbide, cobalt tool and filled them with molybdenum disulfide (a solid lubricant) and tested them while turning hardened steel and performance is compared with conventional tool.…”
Section: Introductionsupporting
confidence: 68%
“…Also, during the development of adaptive smart machining when using smart cutting tools, there is minimization in the machining time and improvement in surface roughness. 41,42 In this work, the DDCS was deposited on WC-Co tool bit with top-layer nanocrystallinity to enhance its…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Muthuraja et al [73] developed WC cutting tools with a WC-10Co-5CaF 2 and WC-10Co solid lubricant for the dry machining of AISI 1020 steel, which was then compared against unlubricated WC tools. The results revealed that the solid lubricant WC-10Co-5CaF 2 tool exhibited reduced cutting force in all directions during turning.…”
Section: Lubricants On the Tool Substratementioning
confidence: 99%